Agroforestry-based plant diversity and its implications for ecosystem restoration in Gunung Leuser National Park, Indonesia - MASRIZAL SARAAN; RAHMAWATY RAHMAWATY; R. HAMDANI HARAHAP; ENDANG HILMI; DELVIAN DELVIAN; ROBERT SIBARANI (Society for Indonesian Biodiversity, 2025)
Abstract. Saraan M, Rahmawaty, Harahap RH, Hilmi E, Delvian, Sibarani R. 2025. Agroforestry-based plant diversity and its implications for ecosystem restoration in Gunung Leuser National Park, Indonesia. Biodiversitas 26: 6367-6377. The Indonesian government promoted conservation partnership schemes in Gunung Leuser National Park (GLNP) to resolve land-use conflicts while supporting ecosystem restoration and local livelihoods, where communities implement agroforestry that combines native species and Multi-Purpose Tree Species (MPTS). However, empirical evidence on plant diversity and vegetation composition within these systems remains limited. This study analyzes vegetation structure, species composition and plant diversity in conservation partnership areas and assess their contribution to ecosystem recovery, including provides recommendations for sustainable management. Vegetation surveys were conducted on 1-ha plots across three stations representing upper, middle, and lower areas. Species composition, dominance, and diversity were quantified using Importance Value, Shannon–Wiener and Margalef Species Richness Index. The upper area was dominated by native dipterocarps (Dryobalanops aromatica), while lower areas were characterized by cultivated MPTS (Parkia speciosa), reflecting trade-offs between natural regeneration and livelihood-oriented agroforestry practices. Species diversity ranged from moderate to high, with native species concentrated near rehabilitation zones and cultivated species in lower areas, which are intensively managed by communities. Overall, agroforestry within conservation partnership enhances biodiversity, supports ecological recovery, and strengthens livelihoods while offering scalable pathways for integrating restoration and biodiversity enhancement with community-based forest management. Strengthening native-species enrichment is recommended to balance ecological objectives with community needs and guide large-scale restoration policies.